Availability of Male and Female Sexual Health and Fertility Information on National Cancer Institute–Designated Cancer Center Websites. Issue 2 (28th March 2020) - Shah, Tejash; Shin, David
Abstract: Introduction: For the estimated 15 million cancer survivors in the United States, access to accurate information regarding quality of life issues such as sexual health and fertility preservation is a very important part of cancer recovery. Aim: Because National Cancer Institute (NCI)–designated cancer centers (CCs) are leaders of cancer care, we sought to determine the prevalence and quality of information relating to male and female sexual health and fertility on all NCI-designated CC websites. Methods: A total of 70 NCI-designated CC websites listed on www.cancer.gov and divided by geographic regions were carefully analyzed for the presence and quality of male and female sexual health and fertility information. Fisher's exact test was performed to assess for differences between websites. Main Outcome Measure: We determined the number and percentage of NCI-designated CC websites with sexual health and/or fertility information, availability of information by region, and information available for each gender. Results: Sexual health and/or fertility information was accessible on 43 of 63 (68.3%) CC websites and was more prevalent on comprehensive CC compared with non-comprehensive CC websites (37 of 49 [75.5%] vs 6 of 14 [42.9%] websites, respectively; P < .05). NCI-designated CC websites had less information on sexual health compared with that on fertility (24 of 63 [38.1%] vs 41 of 63 [65.1%] websites, respectively; P < .01). Access to data was less available for men compared with women (35 of 41 [85.4%] vs 41 of 41 [100%] websites, respectively; P < .05) on CC websites providing fertility preservation information. Fifteen CCs in the South Atlantic (11) and East South Central (4) regions did not offer sexual health information on their respective websites. Conclusion: Information regarding sexual health and fertility preservation after cancer treatment is not common and less available for men compared with women on NCI-designated CC websites. The aforementioned data highlight the need to improve the quality and accessibility of sexual health and fertility preservation information for all NCI-designated CC websites.